THE USE OF TECHNOLOGIES IN EDUCATION: : CHALLENGES AND POSSIBILITIES FOR THE EDUCATOR - Almeida dos Santos Sousa, Emerson; da Silva Ferreira, Jhonnatas; Souza Costa Ferreira, Manuele; Vinicius de Araújo Silva, Marcos (Revista Gênero e Interdisciplinaridade, 2021)
The use of Information and Communication Technologies is, without a doubt, an excellent teaching strategy aimed at inclusion, innovation and adequacy to the needs of students and the labor market. However, including them in the classroom is not simple. It goes beyond equipping the school with innovative technological resources. It permeates the administration of these resources, including personal devices such as smartphones. Thus, the teacher needs to rethink their way of working in order to use technological instruments as an ally to learning. It is necessary to take some precautions, as technologies bring new challenges to the classroom. In this sense, this article aims to analyze the main challenges and possibilities faced by the teacher when using Information and Communication Technologies in their pedagogical work. For this, we will discuss the great contributions that technology can make to the classroom; we will investigate the main problems of its misuse as a pedagogical resource; and, finally, we will identify the main obstacles faced by teachers regarding its use in the daily school life of a public school in the interior of the state of Bahia. Working with technologies requires planning, commitment, dedication and daring from the educator. We spoke with eight professors from this institution and their responses and attitudes are briefly discussed. Among the main problems related to technology in the classroom, the following were pointed out: cell phone use at inopportune times; poor use of the internet as a research tool and difficulty in handling technologies by educators.Keywords: Technology. Information. Communication. Education.